Predictor of Self-Efficacy, and Working Attitude Working Motivation on Improving quality of services - Adam Barlian Trisnadi; Dian, Wahyuni; Wahidi, Kemala Rita (International Journal of Nursing and Health Services (IJNHS), 2024)
Background: This study was conducted based on the incidence issues of patients’ safety in inpatient room. Objective: The study aimed to examine the association between self-efficacy, and working attitude on quality of services with working motivation as intervening variable. Method: A cross-sectional study was applied in this study. We involved 108 inpatient nurses which are selected using the purposive sampling technique. The statistically analysis using the structure equation modelling. Result: The results found that self-efficacy, and attitude were directly affected on working motivation and quality of services simultaneously (p-value <.05). Conclusion: The effects of self-efficacy and working attitude on the quality of services are significant, with working motivation serving as a critical intervening variable. Recommendation: Hospitals should therefore focus on strategies that enhance all three factors to ensure the delivery of superior healthcare services. Further study needs to conduct the study by developing the intervention to improve the quality of nursing services. Implication: Hospitals should therefore focus on strategies that enhance all three factors to ensure the delivery of superior healthcare services